2013
DOI: 10.1038/npp.2013.209
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Dopamine Induced by Cigarette Smoking: Novel Insights from a [11C]-(+)-PHNO PET Study in Humans

Abstract: Positron emission tomography (PET) has convincingly provided in vivo evidence that psychoactive drugs increase dopamine (DA) levels in human brain, a feature thought critical to their reinforcing properties. Some controversy still exists concerning the role of DA in reinforcing smoking behavior and no study has explored whether smoking increases DA concentrations at the D3 receptor, speculated to have a role in nicotine's addictive potential. Here, we used PET and]oxazin-9-ol) to test the hypothesis that smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 55 publications
(78 reference statements)
3
42
1
Order By: Relevance
“…We, therefore, included ethnicity as a nuisance covariate in a separate analysis, and also conducted an analysis including only participants of Caucasian and Hispanic ethnicities (n = 43), which share similar allele frequencies at the loci examined. Finally, because of the interaction of cigarette smoking with the dopamine system (Brody et al, 2004, Le Foll et al, 2013, smoking status was added as a nuisance covariate in a separate analysis. All statistical images were thresholded at a voxel height of Z42.3 and a cluster-probability threshold of po0.05, corrected for whole-brain multiple comparisons using the Theory of Gaussian Random Fields.…”
Section: Image Analysismentioning
confidence: 99%
“…We, therefore, included ethnicity as a nuisance covariate in a separate analysis, and also conducted an analysis including only participants of Caucasian and Hispanic ethnicities (n = 43), which share similar allele frequencies at the loci examined. Finally, because of the interaction of cigarette smoking with the dopamine system (Brody et al, 2004, Le Foll et al, 2013, smoking status was added as a nuisance covariate in a separate analysis. All statistical images were thresholded at a voxel height of Z42.3 and a cluster-probability threshold of po0.05, corrected for whole-brain multiple comparisons using the Theory of Gaussian Random Fields.…”
Section: Image Analysismentioning
confidence: 99%
“…In humans, tobacco use has been associated with both increased striatal dopamine synthesis capacity (Salokangas et al, 2000) and dopamine release in response to acute cigarette use in smokers (Brody et al, 2004;Le Foll et al, 2013). However, two studies found that acute nicotine use did not elicit a significant dopamine release in smokers (Barrett et al, 2004;Montgomery et al, 2007), although these did find that the subjective hedonic response to acute nicotine was related to dopamine release.…”
Section: Introductionmentioning
confidence: 96%
“…Dopamine (DA) is a neurotransmitter believed to be important in the final common path in drug dependence, including nicotine (Pich et al, 1997). DA is believed to mediate both the rewarding (Brody et al, 2004;Corrigall et al, 1992;Le Foll et al, 2014) and withdrawal-associated (Rada et al, 2001;Rahman et al, 2004) effects of nicotine. That is, increased DA is associated with ratings of positive subjective measures (Montgomery et al, 2007), and decreased DA is believed to mediate the negative state during withdrawal (Hildebrand et al, 1998;Le Foll et al, 2014).…”
Section: Introductionmentioning
confidence: 99%